Analisis Etika dalam Struktur Organisasi dan Tata Kelola di Sekolah SMA St. Gabriel Maumere - Yosefa De Ancieta; Agnes Nona; Rusli Hereng (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This study aims to analyze the organizational structure and governance at SMA ST. Gabriel Maumere in order to improve the efficienchy and effectiveness of educational management at the school.The research method used is a descrtiptive approach with a case study,involving data collection through interviews,observations,and documentation.The findings show that the organizational structure at SMA ST. Gabriel Maumere is well –structured,consisting of clear positions,from the principal to the administarsive staff.The governance at this school operates in a coordinated manner,with clear task divisions and effective communication mechanisms between departments.However there are some challenges in utilizing information technology to support administrive processes and data management.This study recommends the need for increased technology training for administrative staff and strengthening the information system to support more efficient governance.It is expected that SMA ST. Gabriel Maumere will achieve more optimal educational goals and be responsive to changes in the education sector.